2023
DOI: 10.59249/oamt2710
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Cerebrospinal Fluid Investigation in First-episode Psychosis

Abstract: Despite being a reliable first-hand source of data on neuronal pathology, cerebrospinal fluid (CSF) analysis remains an often-overlooked evaluation method in first-episode psychosis (FEP). In this paper, we begin by discussing the current role of CSF testing during FEP evaluation in clinical practice. Given that anti-N-methyl-D-aspartate receptor encephalitis presents with a clinical picture indistinguishable from FEP in >85% of cases, we debate the importance of testing for CSF neuronal antibodies in at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…As such, lumbar puncture (LP) remains a critical component of the diagnostic process in AE. 42 As observed in this case, neopterin has become an increasingly utilized biomarker of neuroinflammation in both AE and other pediatric neuroinflammatory disorders. [43][44][45] A similarly sensitive, but not specific, biomarker of neuroinflammation is neurofilament light chain (NfL), which has been observed in the blood and CSF of multiple neurologic conditions, including AE.…”
Section: Jonathan Santoro MDmentioning
confidence: 69%
See 1 more Smart Citation
“…As such, lumbar puncture (LP) remains a critical component of the diagnostic process in AE. 42 As observed in this case, neopterin has become an increasingly utilized biomarker of neuroinflammation in both AE and other pediatric neuroinflammatory disorders. [43][44][45] A similarly sensitive, but not specific, biomarker of neuroinflammation is neurofilament light chain (NfL), which has been observed in the blood and CSF of multiple neurologic conditions, including AE.…”
Section: Jonathan Santoro MDmentioning
confidence: 69%
“…The blood-brain barrier, when fully intact, prevents discernment of inflammatory disease in the brain by serum testing. As such, lumbar puncture (LP) remains a critical component of the diagnostic process in AE 42 . As observed in this case, neopterin has become an increasingly utilized biomarker of neuroinflammation in both AE and other pediatric neuroinflammatory disorders 43-45 .…”
Section: Jonathan Santoro MDmentioning
confidence: 97%
“…However, others also regarded that single parameter could not be a reliable biomarker (Pav al et al, 2023;Söderlund et al, 2009). Further studies are needed to clarify the mode of action of D-pinitol on neuro-inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In this cycle, glutamate released from neurons is transported into astrocytes, where it converted to glutamine, which is then returned to neurons, where it is subsequently converted to glutamate [ 67 , 68 ]. Analysis of CSF has demonstrated that first-episode psychosis (FEP) and drug-naïve schizophrenia patients have an elevated glutamine-to-glutamate ratio [ 69 , 70 ]. The density of astrocytes expressing the disrupted-in-schizophrenia 1 (DISC1) gene has been reported to be decreased in the dentate gyrus of hippocampus in schizophrenia patients compared to healthy controls [ 71 ].…”
Section: Neuroinflammationmentioning
confidence: 99%